Unmanageable Tourism Destination Brands? - Bodil Stilling Blichfeldt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
Increasingly researchers and practitioners adopt branding to build and manage tourism destination images. However, we have yet to ask the question: Is it pos-sible to build and/or manage destination brands? This crucial question is ad-dressed by means of: (1) recourse to the origins of branding; (2) explication of fundamental differences between such origins and destinations; and (3) e-xemplification by means of resident-tourist interactions. The answer offered by this paper is that destination brands may not be manageable at all or at least, that destination brands are so different from consumer brands that we have to accept that specific elements of destination brands are unmanageable to an ex-tent that questions much of the taken-for-granted destination brand-ingknowledge. Consequently, the paper discusses what branding/brand man-agement can(not) do for destination image building and management.
Keywords: 330; Branding; destination image; resident-tourist interaction; Tourismuswirtschaft; Markenpolitik